Fungsi Museum Subkos sebagai Sumber Belajar Sejarah Siswa di Kota Lubuk Linggau dan Musi Rawas Utara - Ratna Wulan Sari; Andriana Sofiarini (Concept: Journal of Social Humanities and Education, 2024)
The museum is a repository of historical relics that are stored and store stories that can be used as a learning resource to gain knowledge in the past. The purpose of this research is to describe the function of the Subkos Museum as a source of learning for history students in Lubuk Linggau and Musi Rawas. This research uses qualitative methods with descriptive research. The focus of this research, namely: 1. What collections are in the Subkos museum. 2. How does the Subkos Museum function as a source of student history learning in Lubuk Linggau and Musi Rawas 3. What are the obstacles in the history learning process in utilizing the function of the Subkoss Museum as a historical source as a learning resource. This research was conducted at SMA Negeri 5 Lubuklinggau, SMA Negeri Sarulangun Muratara. In this study that is used as a source consists of informants (Head of the Museum, Museum Manager, museum manager, Principal, History Teacher, XI IPS class students, Documents, syllabus, lesson plans, and other documents that can support this research, as well as the place of research. Data collection techniques using interview observation techniques, interactive analysis with the task of analysis stages, namely data reduction, data presentation, and conclusion drawing that interacts with data collection.